(3QSGdI CHh MfjaI aj ePgH Cgd GdSfI hGdLeGYIs - (3GdJjej, Gdchaj, CHh MfjaI, GdfYeGf Hf KGHJ, J (B150 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GYdehG CUMGHj hENhGfj Cf ePgH Ggd GdSfI hGdLeGYI Ydi GKfJj YTQ NUdI aef cGf efce jSJbje Ydi gPg GdNUGd dG jchf eHJOYG hdG UGMH Gdghi (B( (3cPG (B) (3aYdjce CUMGHj hENhGfj HgPg GdNUGd MJi JchfhG aj TaGYI fHjfG Udi Gddg Ydjg hSde jhe GdbjGeI (B: (3fbQ HCf GdEjeGf gh GdEbQGQ HGddSGfs
(3BNQgG (B:s
(3GdcHQi CaVd fSGA GdYGdejf hCe GdeDefjf heWgQI ef GdRfG hHQjFI YeG bGdJ GdQhGaV aef TgO YdjgG HGdRfG agh hdO GdRfG (B( (3cPG (B) (3hCgd GdLfI aj GdLfI NGdOhf hCgd GdfGQ aj GdfGQ NGdOhf dbhdg JYGdi aj Mb GdeDefjf (B{ (3ChdFc CUMGH GdLfI ge ajgG NGdOhf (B} (3haj Mb GdcaGQ (B{ (3ChdFc CUMGH GdfGQ ge ajgG NGdOhf (B}s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8 / 36s
(3eYLe GdeDdajf (B4 / 32s
(3gOjI GdYGQajf (B2 / 495s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJhMjO hGdedd hGdfMds